Principal communication management in improving teacher performance in Senior High School - Maulidin Maulidin; Nasir Usman; Bahrun Bahrun (STAI Hubbulwathan Duri, 2022)
The purpose of this study is to describe how the principal's communication management in improving teacher performance at SMA Banda Aceh. This study uses a descriptive qualitative approach. This research was conducted at SMA Negeri Banda Aceh, namely SMAN 4 which is located in Kuta Alam District, Banda Aceh City. The sample in this study consisted of the Principal, Deputy Principal and Teachers. Data collection techniques using observation, interviews. The standard of data validity in qualitative research refers to the standards of credibility, transferability, dependability, and confirmability. The data analysis technique used is descriptive qualitative analysis with data reduction techniques, data presentation, and drawing conclusions. The results of this study concluded that the pattern of communication between the principal and the teacher council in improving teacher performance. The pattern of communication carried out by the principal has been going well by creating a harmonious family atmosphere in the form of interpersonal communication in the form of primary and secondary and linear communication patterns in improving teacher performance, increasing teacher performance at Banda Aceh High School. Implementation of communication between the head of school and the teacher council in improving teacher performance. The obstacles that occur in communication between the principal and the teacher council are technical communication barriers, and semantic barriers.